2020
DOI: 10.1161/atvbaha.119.313224
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Uric Acid Promotes Atherosclerosis via AMPK (AMP-Activated Protein Kinase)-Mediated Inflammation

Abstract: Objective: Uric acid is supposed but not yet determined to be associated with atherosclerosis. Uric acid is released from damaged cells to form urate crystal, which is recognized by the immune system to produce IL (interleukin)-1. Danger signals and IL-1 have been shown to play an important role in atherosclerosis. We determined whether the physiological level of soluble uric acid promotes inflammation and develops atherosclerosis. Approach and Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 45 publications
3
75
0
Order By: Relevance
“…The molecular mechanism of UAinduced NLRP3/IL-1 b activation is through NF-kB activation and mitochondrial ROS (mROS) ( Figure 2). Consistent with the latest research published by Kimura et al, UA promotes the secretion of IL-1b mediated by NLRP3 inflammasomes via regulating the AMP-activated protein kinase (AMPK)mammalian target of rapamycin (mTOR) mROS and hypoxiainducible factor-1a (HIF-1a) pathway in human peripheral blood mononuclear cells ( Figure 2) (Kimura et al, 2020). In mice treated with uricase gene transfer and XO inhibitor, however, the decrease of UA level promoted the activation of AMPK, and the formation of atherosclerotic plaque was inhibited (Kimura et al, 2020).…”
Section: Ua and Inflammatory Responsesupporting
confidence: 88%
See 2 more Smart Citations
“…The molecular mechanism of UAinduced NLRP3/IL-1 b activation is through NF-kB activation and mitochondrial ROS (mROS) ( Figure 2). Consistent with the latest research published by Kimura et al, UA promotes the secretion of IL-1b mediated by NLRP3 inflammasomes via regulating the AMP-activated protein kinase (AMPK)mammalian target of rapamycin (mTOR) mROS and hypoxiainducible factor-1a (HIF-1a) pathway in human peripheral blood mononuclear cells ( Figure 2) (Kimura et al, 2020). In mice treated with uricase gene transfer and XO inhibitor, however, the decrease of UA level promoted the activation of AMPK, and the formation of atherosclerotic plaque was inhibited (Kimura et al, 2020).…”
Section: Ua and Inflammatory Responsesupporting
confidence: 88%
“…Optical coherence tomography showed a significant increase in plaque rupture in patients with sUA > 8.0 mg/dl (Kobayashi et al, 2018). Recently, Kimura et al demonstrated that UA promotes the secretion of IL-1b mediated by NLRP3 inflammasomes via regulating the AMPK-mTOR mROS and HIF-1a pathway in human peripheral blood mononuclear cells (Kimura et al, 2020). In mice treated with uricase gene transfer and XO inhibitor, however, the decrease of UA level promoted the activation of AMPK and inhibited the formation of atherosclerotic plaque (Kimura et al, 2020).…”
Section: Ua and Chdmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is safe to mention that suppressing inflammation does not necessarily exert protective effects but may also result in maladaptive consequences. Several lines of evidence have demonstrated the extensive involvement of inflammation in both acute and chronic cardiovascular manifestations such as atherosclerosis (Jiang et al, 2020;Kimura et al, 2020), myocardial infarction (Cremer et al, 2020;Tian et al, 2020), hypertension (Jan-on et al, 2020;Park et al, 2020) and heart failure (Molitor et al, 2020;Pop et al, 2020).…”
Section: The Role Of Inflammation In Cardiovascular Diseasesmentioning
confidence: 99%
“…Previous research indicated that the hyperuricemic state in the body mainly promotes the development of CHD via the following aspects: 1) Activates platelets, promotes thrombosis, and activates inflammatory mediators to reduce plaque stability [37][38][39] ; 2) Stimulates NADPH oxidase, leading to the abnormal structure and function of vascular endotheliocytes and affects the production of ATP, resulting in the dysfunction of vascular endotheliocytes [40][41][42][43] ; 3) leads to the precipitation of urate crystals and excessive generation of oxygen free radicals, reduces the stability of plaques [44][45][46] . Yuichi Saito [47] et al pointed out that elevated uric acid level was closely related to vascular endothelial dysfunction in ACS patients, which may further cause poor prognosis.…”
Section: Discussionmentioning
confidence: 99%